Pengaruh Celebrity Endorser Dan Brand Image Terhadap Keputusan Pembelian Konsumen Di- Youtube Untuk Produk Kosmetik Wardah Dan Maybelline Di Kota Bengkulu - Amirah Herniati Zahra; Sularsih Anggarawati; Praningrum Praningrum (Student Journal of Business and Management, 2023)
The purpose of this study was to examine 1) the effect of Celebrity Endorser on purchasing decisions 2) the effect of Brand Image on purchasing decisions 3) the effect of Celebrity Endorser and Brand Image simultaneously on purchasing decisions. The analysis method used is non probability sampling, namely purposive sampling. Hypothesis analysis using multiple linear regression, coefficient of determination, difference test, t test, and f test. The unit of analysis is respondents who use Wardah cosmetic products and Maybelline cosmetic products in Bengkulu City. The questionnaire that can be processed is 200. The results found that 1) Celebrity endorsers influence purchasing decisions on Wadah and Maybelline products. This means that the more visible and credible the endorser is in promoting the product, the higher the level of purchasing decisions for Wardah and Maybelline cosmetic products 2) Brand image has no effect on purchasing decisions on Wardah cosmetic products. Meanwhile, in Maybelline cosmetic products, brand image affects purchasing decisions. 3) Celebrity endorsers and brand image simultaneously influence purchasing decisions on Wardah and Maybelline cosmetic products. The better the celebrity endorser and attractive brand image, the higher the purchasing decision. This means that the more attractive the endorser promotes the product and has an attractive brand image, the higher the level of purchasing decisions for Wardah and Maybelline cosmetic products.